The First Public Congress ofthe Kherson Region Phytobyologists (April 6, 2006, Kherson) (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
The First Public Congress ofthe Kherson Region Phytobyologists (April 6, 2006, Kherson)